The epidemiology of knee injuries in Iranian male professional soccer players - Rahnama, N.; Bambaeichi, E.; Daneshjoo, A. (Sport Sciences for Health, 2009)
Detailed injury epidemiology is an invaluable tool for minimising risk associated with sporting injuries. The aim of this study was to investigate epidemiology of knee injuries in Iranian male professional soccer players. In total, 390 soccer players of 16 clubs were studied during one season. A total of 43 injured soccer players were interviewed and 16 team physicians were consulted. All information was collected through standard questionnaires. Furthermore, medical personal prospectively reported time-loss injuries sustained by players over one season and the knee injuries were evaluated. The results showed that in total, from 390 players, 43 of them suffered knee injuries (14.9 per 100 players). The anterior cruciate ligament was the most commonly injured ligament of the knee, in which 12.5% were accompanied by injuries to the medial meniscus and medial collateral ligament. There was a significant difference in incidence of injury between the preferred (62.9%) and non-preferred leg (37.1%). Most injuries were characteristically severe (82.3%). Most injuries occurred in away games (52.94%), mostly in the second half and most commonly in the final 15 min (35.3%). The incidence of non-contact injuries (66.12%) was significantly higher than contact injuries (33.87%). It can be concluded that the incidence of knee injury was high (0.12 injuries per team per match). Injury tends to be more common in match play and mostly at the end of season. Midfielders suffered more knee injuries. Most injuries occurred in the losing teams.